Visible and infrared properties of unaltered to weathered rocks from Precambrian granite-greenstone terrains of the West African Craton. (December 2015) - Metelka, Václav; Baratoux, Lenka; Jessell, Mark W.; Naba, Séta
Abstract: In situ and laboratory 0.35 μm–2.5 μm spectra of rocks from a Paleoproterozoic granite-greenstone terrain along with its Neoproterozoic sedimentary cover and derived regolith materials were examined in western Burkina Faso. The reflectance spectra show the influence of typical arid to semi-arid weathering with the formation of desert varnish, iron films, and dust coatings. Fe and Mg–OH absorption features related to chlorite, amphibole, pyroxene, epidote, and biotite are observable in the mafic and intermediate meta-volcanic rocks as well as in the granodiorites and tonalites. Al–OH absorption caused by kaolinite, smectite, illite/muscovite are typical for meta-volcano-sedimentary schists, Tarkwaian-type detrital meta-sediments, sandstones of the Taoudeni basin, all of the weathered surfaces and regolith materials. Ferric and ferrous iron absorptions related to both primary rock-forming minerals and secondary weathering minerals (goethite, hematite) were observed in most of the sampled materials. The results show that although weathering alters the spectral signature of the fresh rock, indicative absorption features located in the short wave infrared region remain detectable. In addition, spectra of soils partially reflect the mineral composition of the weathered rock surfaces. The analysis of the hyperspectral data shows the potential of differentiating between the sampled surfaces. The library presents a primary database for the geological and regolith analysis of remote sensing data in West Africa. Highlights: We have measured infrared spectra of rocks from the West African craton. We have assessed the effect of weathering on the infrared spectra of rocks. Weathering alters the spectral signature of the rocks but indicative absorptions remain. We provide reference spectral data for Precambrian rocks of the West African Craton.